Determination of the head loss through a pipe-chamber junction using computational fluid dynamics - Cruz, Laurenz Luigi B.
The configured pipe-chamber junction was modeled using Computational Fluid Dynamics. CFD results were verified by comparing the results of the simulation to Sangster' s experimental data. The simulations resulted to NRMSD value of around 6% for the inlet to outlet loss and 12% for the lateral to outlet loss. Parameters such as the diameter ratio of the inlet and middle outlet pipes and the spacing between the pipes were varied throughout the simulation. Graphs relating the pressure loss coefficients to the diameter ratio, and the spacing of the pipes were acquired from numerous simulations. The acquired graphs of the loss coefficients were used to solve the total pressure loss for the proposed by-pass structure. The graphs can also be used to aid the solution for the head loss through a chamber with different geometric properties.